Burden of Proof in Bioethics. (November 2015) - Koplin, Julian J.; Selgelid, Michael J.; Dawson, Angus; Ballantyne, Angela
Abstract A common strategy in bioethics is to posit a prima facie case in favour of one policy, and to then claim that the burden of proof (that this policy should be rejected) falls on those with opposing views. If the burden of proof is not met, it is claimed, then the policy in question should be accepted. This article illustrates, and critically evaluates, examples of this strategy in debates about the sale of organs by living donors, human enhancement, and the precautionary principle. We highlight general problems with this style of argument, and particular problems with its use in specific cases. We conclude that the burden ultimately falls on decision‐makers (i.e. policy‐makers) to choose the policy supported by the best reasons.